Food security and the right to food: finding balance in the 2012 Food Assistance Convention - La Chimia, Annamaria (Cambridge University Press, 2016)
On 25 April 2012, after years of negotiations delayed by halts and setbacks, the Food Assistance Convention was adopted—the latest in a series of agreements that since 1967 have regulated the international provision of food aid. Great expectations have been placed on the adoption of the Convention. In particular it was hoped that the Convention would answer the call for a new system of food aid governance, introduce more effective mechanisms to address world's food insecurity and, ultimately, improve and modernize the rules applicable to food aid. This article provides the first critical commentary of the Convention's text, assesses the strengths and weaknesses of its provisions and considers whether and how the Convention has modified the architecture of international food aid regulation. The article also indicates where amendments to the rules might be needed to make the international regulation of food aid more effective. The article concludes that the Convention is, on balance, a positive instrument that could improve governance and adequacy of food assistance. The Convention is also important for the international human rights discourse on how States can fulfil their obligation to assist countries in need in that it offers guidance on how to meet such obligation in the specific context of the right to food. States should therefore be urged to sign and ratify it.